RELATIONSHIP BETWEEN CHARACTERISTICS OF PREGNANT WOMEN AND KNOWLEDGE OF DANGER SIGNS IN PREGNANCY - Nora Rahmanindar; Ilma Ratih Zukrufiana (Siklus : Journal Research Midwifery Politeknik Tegal, 2026)
Danger signs of pregnancy are conditions that require early detection to prevent maternal and neonatal complications. Pregnant women's knowledge of danger signs of pregnancy is related to various individual characteristics. This study aims to determine the relationship between age, education, occupation and parity of pregnant women with knowledge of danger signs of pregnancy. This study uses an analytical design with a cross-sectional approach. The population in this study were all pregnant women who checked their pregnancy, a total of 59 respondents, the total sampling technique, using a questionnaire and analyzed univariate and bivariate using the Chi square test. The results showed that most respondents were 21-35 years old (78%), had a high school education (66.1%), were unemployed (52.5%) and had multigravida parity (49.2%). Bivariate analysis showed a significant relationship between the age of pregnant women with knowledge of danger signs of pregnancy (P = 0.000), education with knowledge (P = 0.000), occupation with knowledge (P = 0.001), and parity with knowledge (P = 0.000). It can be concluded that age, education, employment status, and the number of pregnant women employed are significantly related to knowledge of pregnancy danger signs. Therefore, more targeted efforts are needed to improve health education, especially for pregnant women with low-risk characteristics and knowledge, through outreach activities and mentoring by health workers.